Women's Attitude Towards Engaging in Sports Activities in The Sultanate of Oman: Together towards engaging in sports activities (from Feb to Sep 2023) - Alsiyabi, Alya Masaud Hamdoon (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to identify Omani women's attitudes towards engaging in sports activities in the Sultanate of Oman, from physical, psychological, and social perspectives. It also aimed to understand the nature of the differences in Omani women attitudes based on their ages. Quantitative method was used to achieve the objectives of this study. A questionnaire was designed, including three main variables: the physical, the psychological, and the social variable. The study sample consisted of 202 Omani women from Wilayat Samail in the Sultanate of Oman in2023.The results indicated that Omani women's attitudes towards engaging in sports activities were positive, with an average score of (3.63). The highest rank was the physical variable with an average score of (4.07), followed by the psychological variable with an average score of (3.71). Meanwhile, the social variable was neutral with an average score of (3.19). The study also concluded that there were no statistically significant differences in Omani women's attitudes towards physical activity based on the variable of age. The researcher recommends further encouragement of the positive attitudes of Omani women towards engaging in sports activities to make physical and sports activities a lifestyle choice for a healthier society. In addition, speeding the awareness on the importance of physical and sport activities is needed via different means, such as, organizing seminars, conferences, workshops, and training sessions in specialized institutions in the sports field across various regions of the Sultanate of Oman.
Keywords: attitudes; sports activities; Omani women